2016
DOI: 10.1080/02652048.2016.1267812
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid conjugated and Ag-carrying organoclay nanoparticles and their response to L929 fibroblast and DLD-1 cancer cells

Abstract: This work presents the synthesis and characterisation of intercalated nanocomposites (NCs) from dispersed water solution blends of octadecyl amine-montmorillonite (ODA-MMT) (NC-0), folic acid (FA) conjugated ODA-MMT (NC-1) and Ag-MMT clay as a stable silver carrying agent (NC-2). The composition, chemical/physical and morphology of NCs with in situ intercalating nanostructures were investigated. Effect of organoclay, FA and Ag-MMT on L929 fibroblast (control), human colon carcinoma (DLD-1) cell lines, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The effect of BAE was evaluated on MC38 tumour cells and normal cells. As L929 cells are frequently used as normal control cells to detect apoptotic effects [ 30 32 ], we used L929 cells as the model of normal cells. According to the data in the literature [ 2 , 33 , 34 ] and the experimental results of IC50 (Table S 2 ), four doses (100, 200, 500 and 1000 μM) of ANC were used for the MTT assays.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of BAE was evaluated on MC38 tumour cells and normal cells. As L929 cells are frequently used as normal control cells to detect apoptotic effects [ 30 32 ], we used L929 cells as the model of normal cells. According to the data in the literature [ 2 , 33 , 34 ] and the experimental results of IC50 (Table S 2 ), four doses (100, 200, 500 and 1000 μM) of ANC were used for the MTT assays.…”
Section: Resultsmentioning
confidence: 99%
“…Folic acid or its conjugates reversibly bind with the FRs, which are abundantly present on the cancer cell surface and easily penetrate through cellular membrane by receptor mediated endocytosis. , Recently, it has been reported that FA successfully forms conjugates with quantum dots, iron oxide NPs, gold NPs, and others. Such conjugates have been widely used in cancer cell targeting, tumor imaging, and drug delivery. , , …”
Section: Introductionmentioning
confidence: 99%
“…Rzayev et al described the synthesis of antibacterial polymer thin films containing silver cations. Intercalated nanocomposites, in which FA conjugated with octadecyl amine-montmorillonite (ODA-MMT) and Ag-montmorillonite (Ag-MMT) due to electrostatic interactions, formed multilayer composite . The therapeutic effect demonstrated on L929 fibroblasts and DLD-1 cancer cells was achieved via interaction of amine groups with DNA–COOH sites and complexing of DNA with silver NPs under the formation of DNA–COOH···Ag complexes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations